Identification of a respiratory-type nitrate reductase and its role for survival of mycobacterium smegmatis in wayne model - Khan, Arshad; Sarkar, Dhiman (Microbial Pathogenesis, 2006)
Nitrate reductase (NR) is found to be expressed in certain mycobacterium sp. whose link with the development of persistence is yet to be resolved. The present study demonstrates the action of selective inhibitors on NR as well as in the survival of Mycobacterium smegmatis using Wayne's model. During gradual shift down to anaerobic stage in Wayne's model, conversion of nitrate to nitrite became apparent in M. smegmatis. More than 97 percent inhibition was observed for the conversion of nitrate to nitrite by azide (0.05 mM) and thiocyanate (20 mM) in both whole-cell as well as its cell-free lysate, respectively. Under identical condition, chlorate (20 mM) inhibited nitrate reduction by 67 and 10 percent, respectively. At these concentrations, neither of azide, thiocyanate nor chlorate had any significant effect on cell growth under aerobic condition. In Wayne's culture model, thiocyanate and chlorate inhibited the growth of M. smegmatis by almost 2 logs at the same concentrations whereas azide inhibited by almost 1.75 log when added at the time of inoculation. Exposure of same culture at 96 h after inoculation in Wayne's model to these inhibitors showed 1.74, 1.95 and 2.37 log inhibition of viable cells with respect to azide, thiocyanate and chlorate. These findings further indicated that NR inhibitors kill the bacilli at anaerobic stage under the experimental condition mentioned. Metronidazole (MTZ) (2 mM) and Nitrofurantoin (NIT) (0.3 mM) reduced the cell number at both stages by < 0.7log. They did not have any effect on NR. Altogether, the results clearly indicate that NR-specific inhibitors could become more promising in killing the bacilli at anaerobic stage than the available conventional drugs. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Mycobacterium smegmatis; nitrate reductase; Wayne model

Intrinsic therapeutic and biocatalytic roles of ionic liquid mediated self-assembled platinum-phytase nanospheres - Soni, Sarvesh K.; Sarkar, Sampa; Selvakannan, P. R.; Sarkar, Dhiman; Bhargava, Suresh Kumar (RSC Advances, 2015)
We herein report the inherent antitumor efficiency of self-assembled phytase enzyme nanospheres and enhance their efficiency by decorating with platinum nanoparticles and with the anticancer drug curcumin. Firstly, controlled self-assembly of phytase enzyme in an Ionic Liquid 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4], led to the formation of therapeutically active phytase nanospheres. These nanospheres were further decorated with platinum nanoparticles by adding the platinum ions to these spheres and the nanoparticles formation was mediated by the specific interaction between the histidine residue (in active site of phytase enzymes) and the platinum ions and subsequent reduction of the ions into nanoparticles. The enzyme spheres act as a functional soft template for the as-formed platinum nanoparticles. These Platinum decorated hybrid biomacromolecular phytase nanospheres were loaded with the anticancer drug curcumin and all the different kinds of nanospheres were subjected to in vitro cytotoxicity for their anticancer effect on three different kinds of cancer cell lines i.e. MCF-7, Hep-G2 and THP-1 derived human macrophages. We observed a gradual increase in the anticancer effect caused by only phytase nanospheres (25%), platinum-phytase nanospheres (37%), phytase-curcumin (78%) and platinum-phytase-curcumin nanospheres (90%) that establishes this protein based system as a robust combinatorial drug delivery vehicle. The platinum-phytase spheres also proved their usability as a highly efficient green and reusable biocatalytic system for phytate degradation. The present work facilitates our understanding of ionic liquid based synthesis for multifunctional protein based drug delivery vehicles incorporating combinatorial chemotherapy for potential application as biopharmaceutical agents for tumor treatment and bio-catalysis.

In vitro and ex vivo antitubercular activity of diarylheptanoids from the rhizomes of alpinia officinarum hance - Honmore, Varsha S.; Rojatkar, Supada R.; Nawale, Laxman U.; Arkile, Manisha A.; Khedkar, Vijay M.; Natu, Arun D.; Sarkar, Dhiman (Natural Product Research, 2016)
Phytochemical investigation of methanol extract of the rhizomes of Alpinia officinarum Hance afforded four known diarylheptanoids 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 5-hydroxy-7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl-3-heptanone (3), and 7-(4 ''-hydroxy-3 ''-methoxyphenyl)-1-phenyl heptan-3-one (4).The acetate derivative of (4), 7-(4 ''-actetate-3 ''-methoxy phenyl)-1-phenyl heptan-3-one (5), was prepared. These diarylheptanoids exhibited promising in vitro and ex vivo antitubercular activity for the first time against dormant Mycobacterium tuberculosis H37Ra with the IC50 values between 0.3447.69 and 0.1322.91 mu M, respectively. All compounds showed comparable activity against Mycobacterium bovis BCG (dormant phage) and did not show any activity against two gram + ve and two gram -ve bacterial strains. These compounds were also weakly cytotoxic up to 300 mu M against three human cancer cell lines THP-1, Panc-1 and A549.

Isolates of alpinia officinarum hance as COX-2 inhibitors: evidence from anti-inflammatory, antioxidant and molecular docking studies - Honmore, Varsha S.; Kandhare, Amit D.; Kadam, Parag P.; Khedkar, Vijay M.; Sarkar, Dhiman; Bodhankar, Subhash L.; Zanwar, Anand A.; Rojatkar, Supada R.; Natu, Arun D. (International Immunopharmacology, 2016)
Background: Inflammation triggered by oxidative stress can cause various ailments, such as cancer, rheumatoid arthritis, asthma, diabetes etc. In the last few years, there has been a renewed interest in studying the antioxidant and anti-inflammatory action of plant constituents such as flavonoids and diarylheptanoids. Aim: To evaluate the antioxidant, anti-inflammatory activity and the total phenolic content of isolated compounds from Alpinia officinarum rhizomes. Furthermore, molecular docking was performed to study the binding mode of these compounds into the active site of cyclooxygenase-2 (COX -2). Methods: A. officinarum rhizomes were extracted by maceration, using methanol. This extract was further fractionated by partitioning with hexane, chloroform and ethyl acetate and these fractions on further purification resulted in isolation of five pure compounds. Characterization was carried out by using H-1 NMR, C-13 NMR and MS. They were further evaluated for antioxidant and anti-inflammatory activity using carrageenan-induced paw edema model in rats. Molecular docking study was performed using Glide module integrated in Schrodinger molecular modeling software. Results: The compounds were identified as 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 3,5,7-trihydroxyflavone (Galangin, 3), 3,5,7-trihydroxy-4'-methoxyflavone (Kaempferide, 4) and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone (5). The compound-3 and compound-5 (10 mg/kg) showed significant (p < 0.001) antioxidant and anti-inflammatory potential. Moreover, total phenolic content was detected as 72.96 mg and 51.18 mg gallic acid equivalent respectively. All the five isolates were found to be good binders with COX-2 (average docking score -9.03). Conclusions: Galangin and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone exhibited anti-inflammatory and in-vitro antioxidant activity which may be due to presence of phenolic content in it. The molecular docking study revealed that these compounds have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors. The results obtained in this work justify the use of A. officinarum in the treatment of inflammatory disorders like rheumatoid arthritis and inflammatory bowel diseases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 5-Hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone; Alpinia officinarum; Anti-inflammatory; Antioxidant; COX-2 inhibitors; Galangin

In silico studies, synthesis and antitubercular activity of some novel quinoline - azitidinone derivatives - Chitre, Trupti S.; Asgaonkar, Kalyani D.; Vikhe, Amrut B.; Patil, Shital M.; Garud, Dinesh R.; Khedkar, Vijay M.; Sarkar, Dhiman; Nawale, Laxman U.; Yeware, Amar (Current Computer-Aided Drug Design, 2021)
Background: Diarylquinolines like Bedaquiline have shown promising antitubercular activity by their action of Mycobacterial ATPase. Objective: The structural features necessary for a good antitubercular activity for a series of quinoline derivatives were explored through computational chemistry tools like QSAR and combinatorial library generation. In the current study, 3-Chloro-4-(2-mercaptoquinoline-3-yl)-1-substitutedphenylazitidin-2-one derivatives have been designed and synthesized based on molecular modeling studies as anti-tubercular agents. Methods: 2D and 3D QSAR analyses were used to designed compounds having a quinoline scaffold. The synthesized compounds were evaluated against active and dormant strains of Mycobacterium tuberculosis (MTB) H37 Ra and Mycobacterium bovis BCG. The compounds were also tested for cytotoxicity against MCF-7, A549 and Panc-1 cell lines using MTT assay. The binding affinity of designed compounds was gauged by molecular docking studies. Results: Statistically significant QSAR models generated by the SA-MLR method for 2D QSAR exhibited r(2) = 0.852, q(2) = 0.811, whereas 3D QSAR with SA-kNN showed q(2) = 0.77. The synthesized compounds exhibited MIC in the range of 1.38-14.59(mu g/ml). These compounds showed some crucial interaction with MTB ATPase. Conclusion: The present study has shown some promising results which can be further explored for lead generation.
Keywords: combilib; Molecular docking; mycobacterial ATPase; QSAR; Quinoline

In vitro antitubercular screening and in silico study of germacradienolide from blainvillea latifolia - Honmore, Varsha; Kalyankar, Vidya; Natu, Arun; Khedkar, Vijay; Sarkar, Dhiman; Rojatkar, Supada (Asian Journal of Chemistry, 2021)
Bioassay-guided isolation from acetone extract of Blainvillea latifolia yielded one compound. The acetone extract, fractions and the compound 1 were investigated for antitubercular activity against Mycobacterium tuberculosis H37Ra. Compound 1 showed the activity with IC50 and MIC values at 8.9 and >100 μg/mL. However, the acetone extract of Blainvillea latifolia was inactive against two Gram negative (E. coli, P. flurescence) and two Gram-positive (S. aureus, B. subtilis) bacterial strains. Hence, it was concluded that the extract and the compound 1 are specifically active against MTB and not against bacterial strains. Molecular docking study was performed against crucial mycobacterial target MtInhA to gain an insight into the binding mode and the thermodynamic interactions governing the binding affinity of this molecule.

Inhibition of amyloid β1-42 peptide aggregation by newly designed cyclometallated palladium complexes - Saini, Rahul; Navale, Govinda R.; Singh, Sain; Singh, Haobam Kisan; Chauhan, Rahul; Agrawal, Sonia; Sarkar, Dhiman; Sarma, Manabendra; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Uncontrolled amyloid aggregation is a frequent cause of neurodegenerative disorders such as prions and Alzheimer's disease (AD). As a result, many drug development approaches focus on evaluating novel molecules that can alter self-recognition pathways. Herein, we designed and synthesized the cyclometallated pyrene (Pd-1 and Pd-3) and anthracene (Pd-2) based palladium complexes ([Pd((L-1)Cl] Pd-1, [Pd(L-2)Cl](Pd-2), and [Pd(L-3)Cl] (Pd-3)). This study explores the effect of these complexes on the aggregation, fibrillation, and amyloid formation of bovine serum albumin (BSA) and A beta(1-42) peptide. Several spectroscopic methods were used to characterize all the Pd-complexes, and the molecular structure of Pd -3 was determined by X-ray crystallography. The secondary structures were studied using circular dichroism (CD) and transmission electron microscopy (TEM), while am-yloid aggregation and inhibitory activities were investigated using the Thioflavin-T (ThT) fluorescence assay. Molecular docking of the Pd-complex (Pd-3) was done using fibril (PDB: 2BEG) and monomeric (PDB: 1IYT) peptides using Auto-dock Vina. As a result, the hydrogen bonding and hydrophobic interaction between the aromatic rings of the Pd-complexes and the amino acids of amyloid-beta peptides significantly reduced the pro-duction of ordered beta-sheets of amyloid fibrils and protein aggregation in the presence of Pd-2 and Pd-3 complexes.
Keywords: A beta(1-42) peptide; Aggregation and molecular docking; Palladium complex